Etiologies and predictors of 30‐day readmissions in patients undergoing percutaneous mechanical circulatory support–assisted percutaneous coronary intervention in the United States: Insights from the Nationwide Readmissions Database. Issue 4 (26th April 2018) - Bavishi, Chirag; Lemor, Alejandro; Trivedi, Vrinda; Chatterjee, Saurav; Moreno, Pedro; Lasala, John; Aronow, Herbert D.; Dawn Abbott, J.
Abstract : Background: Patients undergoing percutaneous mechanical circulatory support (pMCS)‐assisted percutaneous coronary intervention (PCI) represent a high‐risk group vulnerable to complications and readmissions. Hypothesis: Thirty‐day readmissions after pMCS‐assisted PCI are common among patients with comorbidities and account for a significant amount of healthcare spending. Methods: Patients undergoing PCI and pMCS (Impella, TandemHeart, or intra‐aortic balloon pump) for any indication between January 1, 2012, and November 30, 2014, were selected from the Nationwide Readmissions Database. Patients were identified using appropriate ICD‐9‐CM codes. Clinical risk factors and complications were analyzed for association with 30‐day readmission. Results: Our analysis included 29 247 patients, of which 4535 (15.5%) were readmitted within 30 days. On multivariate analysis, age ≥ 65 years, female sex, hypertension, diabetes, chronic lung disease, heart failure, prior implantable cardioverter‐defibrillator, liver disease, end‐stage renal disease, and length of stay ≥5 days during index hospitalization were independent predictors of 30‐day readmission. Cardiac etiologies accounted for ~60% of readmissions, of which systolic or diastolic heart failure (22%), stable coronary artery disease (11.1%), acute coronary syndromes (8.9%), and nonspecific chest pain (4.0%) were the most common causes. In noncardiac causes, sepsis/septic shock (4.6%), hypotension/syncope (3.2%), gastrointestinal bleed (3.1%), and acute kidney injury (2.6%) were among the most common causes of 30‐day readmissions. Mean length of stay and cost of readmissions was 4 days and $16 191, respectively. Conclusions: Thirty‐day readmissions after pMCS‐assisted PCI are common and are predominantly associated with increased burden of comorbidities. Reducing readmissions for common cardiac etiologies could save substantial healthcare costs.